(GEO)POLITICAL ASPECTS OF THE POSITION OF REPUBLIC OF SERBIA – THIRTY YEARS OF THE DAYTON PEACE AGREEMENT (Heritage, 2025)
The authors analyze the position of the Republika Srpska thirty years after the Dayton Peace Agreement, with a special emphasis on (geo)political aspects. Considering that 2025 marks the thirtieth anniversary of the signing of the Dayton Peace Agreement, we believe that it is both scientifically and socially justified to address this topic, both from a certain historical distance and through an analysis of current events concerning the position of the Republika Srpska and the Serbian people in Bosnia and Herzegovina. The introduction is devoted to a brief historical overview of the change in the ethnic structure and the weakening of the position of the Serbian people in Bosnia and Herzegovina from World War II to the war-torn 1990s. Then, through a contextual analysis, we present international initiatives and acts from 1992 to 1995 that preceded the signing of the Dayton Agreement. The central part of the paper is dedicated to a descriptive and explanatory analysis of the position of the Republika Srpska in the decades after the signing of the peace agreement. The emphasis is on the period from 2021 to 2025, with the aim of presenting (geo)political aspects 30 years later. We will use methods of analysis and synthesis to describe and explain the processes that took place in the observed area, as well as the geopolitical method necessary for understanding the position of the state in the regional and international context. By analyzing available documents and relevant literature, we will collect the necessary data related to the subject of research.
Keywords: Dayton Peace Agreement; Republika Srpska; Bosnia and Herzegovina; geopolitics; security